1995
DOI: 10.1182/blood.v86.2.451.bloodjournal862451
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cyclophosphamide, carmustine (BCNU), and etoposide (VP16-213) with or without cisplatin (CBV +/- P) and autologous transplantation for patients with Hodgkin's disease who fail to enter a complete remission after combination chemotherapy

Abstract: Patients with Hodgkin's disease (HD) who fail to enter a complete remission after an initial course of combination chemotherapy are usually considered to have an induction failure (IF); this subset of patients has an extremely poor outcome with further conventional therapy. Since 1985, we have entered 30 IF patients into protocols using conditioning with high-dose cyclophosphamide, carmustine (BCNU), and etoposide (VP16–213) with or without cisplatin (CBV +/- P) followed by autologous stem cell transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(33 citation statements)
references
References 17 publications
1
29
0
3
Order By: Relevance
“…An analysis of treatment outcome in primary progressive patients showed that the 5‐year freedom from failure and overall survival for all patients were 17% and 26%, respectively, compared to 31% and 43% for those treated with HDCT and an ASCT . Other studies have further confirmed that patients receiving HDCT followed by ASCT have a better outcome than patients treated with chemotherapy . However, a majority of these patients still relapse following HDCT and ASCT.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…An analysis of treatment outcome in primary progressive patients showed that the 5‐year freedom from failure and overall survival for all patients were 17% and 26%, respectively, compared to 31% and 43% for those treated with HDCT and an ASCT . Other studies have further confirmed that patients receiving HDCT followed by ASCT have a better outcome than patients treated with chemotherapy . However, a majority of these patients still relapse following HDCT and ASCT.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Numerous centers throughout North America and Europe currently administer adjuvant RT to their patients undergoing HDCT and stem cell rescue (SCR) . The rationale underlying this approach is that patients treated with HDCT alone have a high rate of failure in sites of prior and/or persistent disease [5,7,8,13,17,27,28]. We [28] and others [24][25][26] have demonstrated that adjuvant RT significantly decreases the risk of relapse in these sites and, in select patients, may improve survival.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy exists, however, over the radiation treatment volume in these patients. We [28] and others [3][4][5][6][7][8][9][10][11][13][14][15][16][17][20][21][22][23][24][25][26] have used localized volumes encompassing solely sites of prior and/or persistent disease (involved-field RT, IFRT). In contrast, Yahalom and co-workers at the Memorial Sloan Kettering Cancer Center (MSKCC) have advocated more comprehensive treatment volumes, i.e., total lymphoid irradiation (TLI), to decrease relapse in new nodal sites [1,19,29].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of treatment outcome in primary progressive patients showed that the 5‐year freedom from failure and OS for all patients were 17 and 26%, respectively, compared to 31 and 43% for those treated with HDCT and an ASCT . Other studies have further confirmed that patients receiving HDCT followed by ASCT have a better outcome than patients treated with chemotherapy . However, a majority of these patients still relapse following HDCT and ASCT.…”
Section: Management Of Relapsed/refractory Diseasementioning
confidence: 99%